Typology and characteristics of indigenous goats and production systems in different agro-ecological zones of Tanzania - Nguluma, A.; Kyallo, Martina M.; Mekuriaw, Getinet; Loina, R.; Nziku, Z.; Chenyambuga, S.; Pelle, Roger (Springer, 2022)
Tanzania has a goat population of about 24.8 million most of which belong to the Small East African breed distributed in almost all agro-ecological zones. The different goat populations and the production system in which they are raised are not well characterized depriving animal breeders useful information in designing and running improvement and conservation programs. Therefore, the study was conducted in all agro-ecological zones in Tanzania to characterize the indigenous goats and the production system in which they are raised. Data on animals were collected from 688 randomly selected adult female goats and for production system description; 220 households were interviewed. Analysis of variance and discriminant analysis were used on quantitative data, while frequency analysis was used on qualitative data. Income generation and meat production were the primary goat rearing objectives. More than 55% of respondents grazed their animals freely in communal lands where natural pasture was the chief feed resource. Mating was mainly uncontrolled with apron and castration being used by goat keepers as mating control methods. Common diseases were contagious caprine pleural pneumonia and helminthiasis. Feed shortage, prevalence of diseases, and water scarcity were the major goat production constraints. There were morphological variations between and within these goat populations, and based on quantitative data, the goats were categorized into two groups. High twinning was observed in Ujiji and Lindi goats and low for Sukuma. The dominant coat color was plain white in Pare, Gogo, Maasai, and Tanga. Other coat color patterns were mixed black and white for Sukuma, reddish-brown for Lindi, black and reddish-brown for Ujiji, and white and reddish-brown for Pwani and Maasai. High within population variation is observed which is important as it can be used as a basis for genetic improvement through selection.